2009
DOI: 10.1002/art.24740
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for upper‐extremity musculoskeletal disorders in the working population

Abstract: Objective. To assess the relative importance of personal and occupational risk factors for upper-extremity musculoskeletal disorders in the working population. Methods. A total of 3,710 workers (58% men) participating in a surveillance program of musculoskeletal disorders in a French region in 2002-2005 were included. Upper-extremity musculoskeletal disorders were diagnosed by 83 trained occupational physicians performing a standardized physical examination. Personal factors and work exposure were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
4
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 35 publications
10
93
4
16
Order By: Relevance
“…[8] Epidemiologic studies have identified several personal, occupational and psychosocial factors related to the musculoskeletal disorders. [9] Even though the exact pathophysiology of most of these musculoskeletal disorders remains obscure, however, connective tissue disorders, neuropathy or vasculopathy may have a synergistic effect on the increased incidence of musculoskeletal disorders in DM. [10] According to Crispin and Alcocer, prolonged hyperglycemia in uncontrolled diabetic patients results in collagen glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Epidemiologic studies have identified several personal, occupational and psychosocial factors related to the musculoskeletal disorders. [9] Even though the exact pathophysiology of most of these musculoskeletal disorders remains obscure, however, connective tissue disorders, neuropathy or vasculopathy may have a synergistic effect on the increased incidence of musculoskeletal disorders in DM. [10] According to Crispin and Alcocer, prolonged hyperglycemia in uncontrolled diabetic patients results in collagen glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in the literature report that the prevalence of musculoskeletal disorders is greater in women than men [22][23][24][25][26] . It is important to state that women compose the majority of the nursing staff and that this characteristic is due to historical factors 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise and the having only one professional occupation have been related to decreased incidence of musculoskeletal disorders and greater work capacity in nursing professionals 36,37 . Obesity has also been associated with musculoskeletal disorders of the upper limbs 23 , and a high body mass index has been associated with pain complaints in upper and lower extremity joints, as well as the lumbar spine 27 . In the present study, significant pain reduction was evidenced, as assessed by the VNS, in both groups, although no significant differences were found between them.…”
Section: Discussionmentioning
confidence: 99%
“…The higher risk of DQD among women could reflect both biological predispositions (sex effect) and greater exposure to biomechanical repetitive work-related constraints (gender-effect) (28). Previous results regarding all upper-extremity MSD (21) suggest that the gender difference more probably reflects differences in exposure to constraints at work than physiological differences (eg, body size). In most cases, women are more often exposed to tasks requiring dexterity and rapid and repetitive movements of the thumb and fingers because of the gender division of work (13).…”
Section: Petit Le Manac'h Et Almentioning
confidence: 94%
“…In cases of hand-wrist symptoms occurring during the past 12 months, the physician performed a physical examination using a standardized clinical procedure that strictly applied the methodology and clinical tests of the "European consensus criteria document" (20) for DQD and the five other specific upper-extremity MSD surveyed (ie, rotator cuff syndrome, lateral epicondylitis, ulnar tunnel syndrome, carpal tunnel syndrome, and flexor-extensor peritendinitis or tenosynovitis of the forearm-wrist region). [See Roquelaure et al (21) for details]. DQD was diagnosed if (i) there was intermittent pain or tenderness localized over the radial side of the wrist, possibly radiating proximally to the forearm or distally to the thumb, and present currently or for ≥4 days in the preceding 7 days and (ii) Finkelstein's test was positive, with distinct right/left difference.…”
Section: Study Population and Designmentioning
confidence: 99%